Bioleaching of sand by the fungus fusarium oxysporum as a means of producing extracellular silica nanoparticles - Bansal, Vipul; Sanyal, A.; Rautaray, D.; Ahmad, Absar; Sastry, Murali (Advanced Materials, 2005)
A plant pathogenic fungus, Fusarium oxysporum, can be used as a biological model system for the extracellular bioleaching of hollow spherical silica nanoparticles (see Figure) from sand. The room-temperature synthesis of oxide nanomaterials using microorganisms starting from potential waste materials could lead to eco-friendly and economically viable methods for the large-scale synthesis of nanomaterials.

Biological synthesis of stable vaterite crystals by the reaction of calcium ions with germinating chickpea seeds - Rautaray, D.; Sanyal, A.; Bharde, Atul A.; Ahmad, Absar; Sastry, M. (Crystal Growth & Design, 2005)
The total biological synthesis of CaCO3 crystals of the metastable vaterite polymorph at room temperature by simple protein-mediated reaction of aqueous Ca2+ ions with the CO2 generated during the root growth from germinating chickpea (Cicer arietinum) seeds is described. Highly stable vaterite crystals of spherical morphology are obtained, indicating that the proteins secreted from the roots during growth play a crucial role in stabilizing and directing the crystal growth.

Formation of BaCrO4 nano crystallites within thermally evaporated sodium bis-2-ethylhexyl-sulfosuccinate and stearic acid thin films - Rautaray, D.; Sinha, K.; Sainkar, S. R.; Pasricha, R.; Pavaskar, N. R.; Sastry, M. (Journal of the American Ceramic Society, 2005)
This paper describes the growth of barium chromate (BaCrO4) nanocrystallites within thermally evaporated thin films of stearic acid (StA) and sodium bis-2-ethylhexyl-sulfosuccinate by a process of Ba2+ ion entrapment followed by in situ reaction CrO42- ions. Dense spherical assemblies of BaCrO4 nanocrystallites of very uniform size (similar to50 nm) were obtained within the two different host matrices. The spherical assemblies were composed of smaller (ca. 5-10 nm size) BaCrO4 crystals indicating that efficient size control over crystal size may be exercised by the matrix. Contact angle measurements of the BaCrO4-StA and BaCrO4-sodium bis-2-ethylhexyl-sulfosuccinate films indicated that they were hydrophobic, thus pointing to the possible role of hydrophobic interaction between the StA and sodium bis-2-ethylhexyl-sulfosuccinate monolayer-covered BaCrO4 crystals in the assembly process.

Fungus-mediated biosynthesis of silica and titania particles - Bansal, Vipul; Rautaray, D.; Bharde, Atul A.; Ahire, Kedar C.; Sanyal, A.; Ahmad, Absar; Sastry, Murali (Journal of Materials Chemistry, 2005)
The synthesis of inorganic materials by biological systems is characterized by processes that occur at close to ambient temperatures, pressures and neutral pH. This is exemplified by biosilicification in marine organisms such as diatoms while laboratory-based synthesis of silica involves extreme temperature and pH conditions. We show here that silica and titania particles may be produced by challenging the fungus Fusarium oxysporum with aqueous anionic complexes SiF62- and TiF62- respectively. Extra-cellular protein-mediated hydrolysis of the anionic complexes results in the facile room temperature synthesis of crystalline titania particles while calcination at 300 degrees C is required for crystallization of silica.

Heavy-metal remediation by a fungus as a means of production of lead and cadmium carbonate crystals - Sanyal, A.; Rautaray, D.; Bansal, Vipul; Ahmad, Absar; Sastry, Murali (Langmuir, 2005)
We show here that reaction of the fungus, Fusarium oxysporum, with the aqueous heavy-metal ions Pb2+ and Cd2+ results in the one-step formation of the corresponding metal carbonates. The metal carbonates are formed by reaction of the heavy-metal ions with CO2 produced by the fungus during metabolism and thus provide a completely biological method for production of crystals of metal carbonates. The PbCO3 and CdCO3 crystals thus produced have interesting morphologies that are shown to arise because of interaction of the growing crystals with specific proteins secreted by the fungus during reaction. An additional advantage of this approach is that the reaction leads to detoxification of the aqueous solution and could have immense potential for bioremediation of heavy metals. Under conditions of this study, the metal ions are not toxic to the fungus, which readily grows after exposure to the metal ions.

Synthesis of hydroxyapatite crystals using amino acid-capped gold nanoparticles as a scaffold - Rautaray, D.; Mandal, Sujata; Sastry, M. (Langmuir, 2005)
Inorganic composites are of special interest for biomedical applications such as in dental and bone implants wherein the ability to modulate the morphology and size of the inorganic crystals is important. One interesting possibility to control the size of inorganic crystals is to grow them on nanoparticles. We report here the use of surface-modified gold nanoparticles as templates for the growth of hydroxyapatite crystals. Crystal growth is promoted by a monolayer of aspartic acid bound to the surface of the gold nanoparticles; the carboxylate ions in aspartic acid are excellent hinging sites for Ca2+ ions. Isothermal titration calorimetry studies of Ca2+ ion binding with aspartic acid-capped gold nanoparticles indicates that the process is entropically driven and that screening of the negative charge by the metal ions leads to their aggregation. The aggregates of gold nanopartictes are believed to be responsible for assembly of the platelike hydroxyapatite crystals into quasi-spherical superstructures. Control experiments using uncapped gold nanoparticles and pure aspartic acid indicate that the amino acid bound to the nanogold surface plays a key role in inducing and directing hydroxyapatite crystal growth.